A comparative study: impact of screen time on sleep quality among university students and school children - Mohd Kamaruzihan, Nurul Qistina; Soe, May Khin Soe (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2023)
Introduction: Screen time has been found to affect sleep quality negatively. Despite numerous studies proving that poor sleep quality and excessive screen time is prevalent among school children and university students, a comparative study on both age groups is yet to be explored extensively so far. This study focused more on school-aged children and university students, as they are often associated with sleep deprivation. The main objectives are to assess the association between screen time and sleep quality among schoolchildren and university students and to compare the effects of screen time on sleep quality between both age groups. Method: This study was conducted in Kulliyyah of Pharmacy, IIUM Kuantan, and six primary schools around Kuantan involving 100 undergraduate pharmacy students and 100 primary schoolchildren aged 10 to 12 years old. The participants were assessed using a self-administered online questionnaire consisting of demographic background, electronic device use, and Pittsburgh Sleep Quality Index (PSQI). The result was analysed using SPSS 23.0 software— descriptive analysis and Chi-Square test to determine the association between duration of screen time and sleep quality. Results: The mean duration of screen time among the participants is 5.5 hours (± 0.102). 56.5% participants have poor sleep quality. The PSQI score for UG students is significantly higher (mean score 6.7 ± 2.741) compared to children (mean score 5.54 ± 2.812) respectively (p value=0.001). The duration of screen time is weakly related to sleep quality. However, respondents with excessive screen time of more than 12 hours have a higher mean PSQI score. Conclusion: The findings revealed that majority respondents have poor sleep quality, independent of screen time. Further research with larger sample size is suggested for clearer comprehensive results.